Tinjauan Karakteristik Tanah untuk Stabilisasi Lapis Pondasi Perkerasan Jalan - Raharmadi, Bambang (Media Ilmiah Teknik Sipil, 2017)
The procedure carried out is testing the physical and mechanical properties of the soil from the quari of Bukit Batu village and quari of Manyawang hamlet based on the Indonesian National Standard (SNI). The purpose of the preparation of this paper was to determine the physical and mechanical properties of the soil from the quari of Bukit Batu village and quari dusun Manyawang so that it could be used as cement stabilization material. Quari soil test results in Bukit Batu village as deep as 1.5 meters from the ground surface with yellow brown soil color, 14.34% moisture content, 2.637 specific gravity and Manyawang quari dusun 1.25 meters from the ground with brownish yellow soil color water 13.80%, specific gravity 2.635. The grain size distribution test fulfilled the conditions allowed to be used as soil stabilization material for cement with a plasticity index of 5.41%, 6.21% ≤ 10% of the specified conditions (Hicks, 2002) and the soil classification of the USCS system included in the CL-ML group namely non-organic silt, sandy clay with low plasticity and AASHTO were included in group A-4 namely silt clay with low plasticity. Quari compacting test (standard) in the village of Bukit Batu filled the maximum dry (dmax) of the soil 1,860 t / m3, optimum moisture content of 13,30% and Manyawang maximum dry weight (mdmax) of soil 1,860 t / m3, optimum moisture content of 13.30%. Free compressive strength test (UCS) quari in Bukit Batu and Manyawang villages 3,451 kg / cm2, 3,521 kg / cm2 and CBR quari test in Bukit Batu and Manyawang villages CBR 100 9.40%, 8.10% and CBR 95 5.20%, 4.65%.